Analysis of Procedures for Submitting Employee Leave at the Belawan Main Harbormaster Office - Juliana, Sinta; Octavia, Dina (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
The Belawan Main Kesyahbandaran Office is a Technical Implementation Unit under the Directorate General of Sea Transportation, Ministry of Transportation which has duties in accordance with the Minister of Transportation Regulation Number PM 34 of 2012 concerning Organization and Work Procedures of the Belawan Main Kesyahbandaran Office which has the task of carrying out supervision and law enforcement in the field of shipping safety and security, as well as coordinating government activities at the port. In this study the authors analyzed the Leave Submission Procedure at the Belawan Main Kesyahbandaran Office directly, using several methods to obtain data from the office such as conducting interviews and observations. In taking leave, employees of the Belawan Main Kesyahbandaran Office must comply with the applicable flow or procedure and also the Operational Standards. In addition, there are also several obstacles in applying for employee leave which can cause leave applications not to be ACC by superiors / leaders